The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1039/c7cc04283c
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the dual role of ethynylbenziodoxolones in gold-catalyzed C(sp)–C(sp) cross-coupling reactions

Abstract: Reported herein is the gold-catalyzed alkynylation of terminal alkynes using ethynylbenziodoxolones (EBXs), where EBXs serve a dual role as oxidants as well as alkyne transfer agents to access unsymmetrical 1,3-diynes. Hence, the catalytic system requires no external oxidants and is compatible with a broad range of substrates, including those with polar functional groups such as NH, OH and B(OH).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…[204] The methodology may be seen as the Au-catalyzed version of the well-known Cadiot-Chodkiewicz reaction. [206] They used Au(PPh 3 )Cl and phen as the cooperative catalytic systemsf or performing the reactions. It is expected that the Au catalyst, Ag additives, and phenel igands( 1,10-phenanthroline) cooperatively activate the reaction.T wo possible mechanisms for the heterocoupling are shown in Scheme 28.…”
Section: Hypervalent Iodine As the Oxidant For Mediating Au I / Au Iimentioning
confidence: 99%
“…[204] The methodology may be seen as the Au-catalyzed version of the well-known Cadiot-Chodkiewicz reaction. [206] They used Au(PPh 3 )Cl and phen as the cooperative catalytic systemsf or performing the reactions. It is expected that the Au catalyst, Ag additives, and phenel igands( 1,10-phenanthroline) cooperatively activate the reaction.T wo possible mechanisms for the heterocoupling are shown in Scheme 28.…”
Section: Hypervalent Iodine As the Oxidant For Mediating Au I / Au Iimentioning
confidence: 99%
“…As an alkynylated reagent, EBXs have been widely used in an intermolecular alkynylation reaction [3, 9, 10] . For example, EBXs reacted with terminal alkynes to provide 1,3‐diynes under gold‐catalyzed or n BuLi‐promoted condition, which were reported by the groups of Liu, [10a] Patil [3a] and Waser, [10b] respectively (Scheme 1 B). The major drawback of these methods is the formation of one equivalent of “waste” 2‐iodobenzoic acid or (2‐iodophenyl)methanol (Scheme 1 A and B).…”
Section: Figurementioning
confidence: 84%
“…[89] In 2017, Patil and coworkers reported the gold-catalyzed C(sp)À C(sp) alkynylation of terminal alkynes with EBXs to access unsymmetric 1,3-diynes (Figure 15b). [90] They used Ph 3 PAuCl as catalyst and catalytic amount of 1,10phenanthroline as auxiliary ligand. Likewise, the group of Liu also used alkynyl hypervalent iodine reagents in the coupling with terminal alkynes for the synthesis of unsymmetrical 1,3diynes.…”
Section: Coupling Partners With Dual Rolementioning
confidence: 99%
“…Computational studies on the mechanism of this domino reaction revealed that the Au(III) catalyst was the precursor of the active Au(I) catalyst that initiates the Au(I)/Au(III) catalytic cycle [89] . In 2017, Patil and coworkers reported the gold‐catalyzed C(sp)−C(sp) alkynylation of terminal alkynes with EBXs to access unsymmetric 1,3‐diynes (Figure 15b) [90] . They used Ph 3 PAuCl as catalyst and catalytic amount of 1,10‐phenanthroline as auxiliary ligand.…”
Section: Oxidant‐free Au(i)/au(iii) Cross‐coupling Catalysismentioning
confidence: 99%